The Enforcement of the 2009 Law Number 46 on Corruption Court: The Role of Special Corruption Court - Yasmirah Mandasari Saragih; Berlian Berlian (Sriwijaya Law Review, 2018)
The Corruption Court is an independent special court under the General Court.  The objectives of creating the Corruption Court is, inter alia, to adjudicate the corruption cases, to eliminate the interference of other party involves in corruption cases, to keep the Court runs in the right path.  Herein, in the concept of rule of law, justice principle, under the ideology of Five Principles of Pancasila may only work well if it accompanied with other principles of social, economic, political, ideological, ethnic, racial, religious, color, and even gender background. Hence, the Judges have dual function both as sanction giver but also to deter other people not commit the same crime. In this connection, the preventive measures, such as counseling and providing legal information, as well as socialization of Corruption Law are perceived to be urgent as a new method for Indonesian in combating the corruption.   This study is a normative one but employing empirical- juridical approaches. The normative research was conducted to analyze the theoretical matters of legal principles, while the empirical approach employed in the form of observing the behavior of the suspect of corruption.  The findings of the study shows that the Art. 53 of the 2002 Law Number 30 it was in contradiction to The 1945 Constitution for the corruption cases cannot be tried in two different courts. That is the idea of the establishment of the Corruption Court as a special court besides the so-many corruptions committed in Indonesia where the verdict of the District Court is beyond the people’s justice